Association between dietary magnesium intake and pelvic inflammatory disease in US women: a cross-sectional study of NHANES - Chen, Zeru; Wu, Zichun; Zhang, Yuying (Frontiers in Nutrition, 2024)
Background: Pelvic inflammatory disease (PID) is a common gynecological condition associated with significant morbidity and healthcare costs. Emerging evidence suggests that dietary factors, such as magnesium intake, may play a role in PID risk. However, the relationship between dietary magnesium intake and PID risk remains uncertain. This cross-sectional study aimed to investigate the association between dietary magnesium intake and the risk of PID.Examination Survey (NHANES) 2015-2018. Weighted multivariable logistic regression was used to examine the association between dietary magnesium intake and PID. Restricted cubic spline (RCS) analysis was performed to assess the linear and non-linear associations. Subgroup analyses were performed based on baseline characteristics.Results: A total of 3,034 women aged 20-59 were included in the study. Magnesium intake exhibited a significant association with lower PID risk in weighted multivariable logistic regression. Adjusted odds ratios (ORs) for dietary magnesium intake in quartiles Q2(133.12-214.93 mg/day), Q3 (214.93-287.19 mg/day), and Q4 (above 287.19 mg/day) compared to Q1 (below 133.12 mg/day) were 0.48 (95% CI: 0.28-0.82), 0.64 (95% CI: 0.32-1.27), and 0.40 (95% CI: 0.18-0.88), respectively. Stratified analyses showed that significant association between dietary magnesium intake and PID in older subgroup but not in younger subgroup. Additionally, RCS analyses consistently revealed a linear negative correlation between dietary magnesium intake and PID risk.This study reveals a significant negative correlation between dietary magnesium intake and risk of PID, particularly among older individuals. These findings underscore the importance of dietary factors in gynecological health and highlight the potential role of magnesium supplementation in PID prevention strategies.